2009
DOI: 10.1152/ajpheart.01173.2008
|View full text |Cite
|
Sign up to set email alerts
|

Differences in collagen cross-linking between the four valves of the bovine heart: a possible role in adaptation to mechanical fatigue

Abstract: Hydrothermal isometric tension (HIT) testing and high-performance liquid chromatography were used to assess the molecular stability and cross-link population of collagen in the four valves of the adult bovine heart. Untreated and NaBH(4)-treated tissues under isometric tension were heated in a water bath to a 90 degrees C isotherm that was sustained for 5 h. The denaturation temperature (T(d)), associated with hydrogen bond rupture and molecular stability, and the half-time of load decay (t(1/2)), associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…2 Thus, we used 65°C as a threshold for permanent collagen denaturation and determined the area of tissue heated above this temperature. IR imaging reveals that while there is a distinct region of cryo-anchoring present through the full thickness of the leaflet, which stays relatively consistent across all RF energies, heating due to RF ablation dominates the leaflet temperature distribution.…”
Section: Heat Distribution Of Rf Ablation With Cryo-anchoringmentioning
confidence: 99%
“…2 Thus, we used 65°C as a threshold for permanent collagen denaturation and determined the area of tissue heated above this temperature. IR imaging reveals that while there is a distinct region of cryo-anchoring present through the full thickness of the leaflet, which stays relatively consistent across all RF energies, heating due to RF ablation dominates the leaflet temperature distribution.…”
Section: Heat Distribution Of Rf Ablation With Cryo-anchoringmentioning
confidence: 99%
“…1,11,25 Previous study in our laboratory with young adult bovine hearts has shown that the hydrothermal denaturation temperature, T d , of collagen from the four valves varies inversely with the maximum TVP expected for that valve: e.g., T d for pulmonary valves is significantly higher than that for aortic valves. 2 Whether or not these differences in molecular stability are a direct result of the differences in in vivo mechanical loading or due to some inherent differences in tissue structure from valve-to-valve is unknown. Nonetheless, the observation is intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the inflow valves (mitral and tricuspid) arise solely from tissues of the endocardial cushions in the developing heart tube, whereas the outflow valves (aortic and pulmonary) are also derived from immigrating neural crest cells (5,12,20,22,47). On the other hand, higher transvalvular pressures (TVP) in the left side of the heart result in higher tensile stresses in the mitral and aortic valve leaflets (3,32). Therefore, the remodeling response to pregnancy may be valve specific.…”
mentioning
confidence: 99%
“…For instance, Aldous et al (3) found that, valve to valve, collagen denaturation temperature was inversely correlated with increasing TVP. Furthermore, tissue from inflow valves contained significantly less mature and total cross-links compared with outflow valves.…”
mentioning
confidence: 99%
See 1 more Smart Citation